Investigation of potential respiratory adverse effects of micro/nanofibrillated cellulose and cellulose nanocrystals using human lung cell lines. - Pinto, Fátima (2022)
Abstract publicado em: Environ Mol Mutagen. 2022 Aug;63(Suppl 1):72-73. (Abstracts from the 13th International Conference on Environmental Mutagens and 53rd Annual Meeting of the Environmental Mutagenesis and Genomics Society). https://onlinelibrary.wiley.com/toc/10982280/2022/63/S1